З питання визначення методичної похибки контактних перетворювачів температури - Бабіченко, Анатолій Костянтинович; Лисаченко, Ігор Григорович; Деменкова, Світлана Дмитрівна (Національний технічний університет "Харківський політехнічний інститут", 2019)
В статье приведены результаты аналитических исследований по установлению уравнений для расчета коэффициентов теплоотдачи, учитывающих условия теплообмена между измеряемой средой и металлическим защитным зондом термопар и термометром сопротивления. Представленные формулы и методики вычислений позволяют осуществлять анализ условий теплообмена при контактном методе измерения температуры с целью разработки мероприятий для уменьшения методической погрешности.

The article presents the results of analytical studies on the establishment of equations for the calculation of heat transfer coefficients, taking into account the conditions of heat transfer between the measured medium and the metal protective probe of the thermocouple and the resistance thermometer. The presented formulas and calculation methods allow the analysis of heat transfer conditions in the contact method of temperature measurement in order to develop measures to reduce the methodological error.
To the question of determining the methodical error of contact temperature transformers
Keywords: вимірювання температури; умови теплообміну; комп'ютерно-інтегрована система управління; критерій Рейнольдса; критерій Прантля; коефіцієнт теплопровідності рідини